2015
DOI: 10.2119/molmed.2015.00123
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Mechanism for White Adipose Tissue Lipolysis after Thermal Injury

Abstract: Extensively burned patients often suffer from sepsis, a complication that enhances postburn hypermetabolism and contributes to increased incidence of multiple organ failure, morbidity and mortality. Despite the clinical importance of burn sepsis, the molecular and cellular mechanisms of such infection-related metabolic derangements and organ dysfunction are still largely unknown. We recently found that upon endoplasmic reticulum (ER) stress, the white adipose tissue (WAT) interacts with the liver via inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Catecholamines are also major drivers of adipocyte lipolysis. Interestingly, a recent study showed that adipose tissue loss due to septic burn injury could be traced back to a loss in AMPK-dependent inhibition of lipolysis in the adipose tissue (Diao et al, 2015). Interestingly, a recent study showed that adipose tissue loss due to septic burn injury could be traced back to a loss in AMPK-dependent inhibition of lipolysis in the adipose tissue (Diao et al, 2015).…”
Section: Burn Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Catecholamines are also major drivers of adipocyte lipolysis. Interestingly, a recent study showed that adipose tissue loss due to septic burn injury could be traced back to a loss in AMPK-dependent inhibition of lipolysis in the adipose tissue (Diao et al, 2015). Interestingly, a recent study showed that adipose tissue loss due to septic burn injury could be traced back to a loss in AMPK-dependent inhibition of lipolysis in the adipose tissue (Diao et al, 2015).…”
Section: Burn Injurymentioning
confidence: 99%
“…Lipolysis and fatty acid release into the circulation have been shown to be elevated upon burn injury (Williams et al, 2009). Interestingly, a recent study showed that adipose tissue loss due to septic burn injury could be traced back to a loss in AMPK-dependent inhibition of lipolysis in the adipose tissue (Diao et al, 2015). Similar to cachexia, burn injury often presents with elevated levels of inflammatory cytokines such as IL-6 (Abdullahi et al, 2017).…”
Section: Burn Injurymentioning
confidence: 99%
“…For example, mice lacking the IL-6 gene have impaired WAT browning in response to burn injury. Other recent data also support these findings, as prolonged activation of IL-6 signaling induces WAT browning and increases energy expenditure in the context of cancer [71]. It is believed that IL-6 mediates WAT browning during the hypermetabolic response via macrophage polarization, as it has been shown to do so in other metabolic conditions like obesity [35].…”
Section: What Are the Regulators Of Wat Browning During The Hypermetamentioning
confidence: 60%
“…In fact, the activation of the NLRP3 inflammasome in the adipose tissue of burn patients has been implicated in insulin resistance and hyperglycemia [68]. It is believed that SFAs and in particular palmitate, an abundant FFA in the serum of burn patients, can induce the activation of the NLRP3-ASC inflammasome, subsequently causing interleukin 1 (IL-1β) secretion in both hepatocytes and adipocytes [69] [70, 71]. In addition, the enhanced inflammatory environment of obese fat pads has also been associated with tumor growth, through the secretion of cytokines like interleukin 18 [72].…”
Section: Mechanisms Of Metabolic Dysfunction During Hypermetabolism: mentioning
confidence: 99%
“…19,20 Primary antibodies were the same as in Western blotting. 19,20 Primary antibodies were the same as in Western blotting.…”
Section: Immunofluorescent Multi-channel Staining Of Livermentioning
confidence: 99%